Development of a real-time operator training simulator for falling film evaporators : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Engineering and Automation at Massey University - Goodwin, Shane (Massey University, 1999)
The Chinese say, "Experience is the only teacher", while an old Western proverb is "Practice makes perfect". In either form, the notion is identical - the more often a task is performed, or a problem confronted, the better it is handled. In the arena of process control involving human operators, the effects of a mistake can be extremely costly to the company. One way to reduce the frequency and severity of mistakes by an operator is to provide training, ideally on a simulation of the process rather than the process itself. This allows the operator to make mistakes and hopefully learn from them, without the company having to lose revenue, lower efficiency, or produce waste product. An operator normally controls a process by changing the settings in a piece of software, which in turn affects the operation of the plant. However, that control software is operating on a machine which is also perfect for modelling and calculating the responses of the process in question. Software to control a process is readily available in a multitude of incarnations and so are packages designed to create models of a process. Used in conjunction, a model-based simulator can be created in order to train operators.
Keywords: Synthetic training devices; Computer simulation; Evaporators; Evaporation